2022
DOI: 10.1063/5.0092860
|View full text |Cite
|
Sign up to set email alerts
|

Microarrayed human bone marrow organoids for modeling blood stem cell dynamics

Abstract: In many leukemia patients, a poor prognosis is attributed either to the development of chemotherapy resistance by leukemic stem cells (LSCs) or to the inefficient engraftment of transplanted hematopoietic stem/progenitor cells (HSPCs) into the bone marrow (BM). Here, we build a 3D in vitro model system of bone marrow organoids (BMOs) that recapitulate several structural and cellular components of native BM. These organoids are formed in a high-throughput manner from the aggregation of endothelial and mesenchym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Similarly, to recapitulate bone marrow in both normal and tumoral conditions, many different studies have been performed [ 99 , 100 ]. Recent studies have developed bone marrow organoids (BMOs) [ 101 , 102 , 103 ]. Recently, we developed a BMO model that mimics several structural and cellular features of native bone marrow (BM) [ 103 ].…”
Section: Current Source To Generate and Culture In Vitro Tumor Sphero...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, to recapitulate bone marrow in both normal and tumoral conditions, many different studies have been performed [ 99 , 100 ]. Recent studies have developed bone marrow organoids (BMOs) [ 101 , 102 , 103 ]. Recently, we developed a BMO model that mimics several structural and cellular features of native bone marrow (BM) [ 103 ].…”
Section: Current Source To Generate and Culture In Vitro Tumor Sphero...mentioning
confidence: 99%
“…Recent studies have developed bone marrow organoids (BMOs) [ 101 , 102 , 103 ]. Recently, we developed a BMO model that mimics several structural and cellular features of native bone marrow (BM) [ 103 ]. These BMOs were formed from Mesenchymal Stromal Cells (MSCs) and endothelial cells, modeling the migration and integration of leukemic cells within the BM, highlighting the potential of this model as an easily accessible and scalable preclinical model for evaluating the efficacy of potential drugs in personalized medicine.…”
Section: Current Source To Generate and Culture In Vitro Tumor Sphero...mentioning
confidence: 99%
“…PEG-based microwells are increasingly used for generating spheroids. For example, Lutolf and colleagues built an organoid array technology using PEG-based microwells, 66 which were generated using silicon-based soft lithography and PDMS molding. The PDMS molds were then used to imprint thiol-vinylsulfone hydrogel cross-linking (gelatin time ∼15 min).…”
Section: Optimization Of Visible Light-initiated Thiol−mentioning
confidence: 99%
“…In essence, the bone marrow niche represents a special type of blood vessel, and recent studies aimed at recapitulating the development of this environment in vitro. For instance, Giger et al 89 used a microwell-based approach where they coseeded ECs and mesenchymal stem cells to form a spheroid. By performing several titration experiments with regard to mesenchymal stem cells:ECs ratios, the authors showed that the number of self-renewing mesenchymal stem cells was higher in the dual-cell type organoids and thus depended on the presence of ECs.…”
Section: Organotypic Vasculature and Specific Functionsmentioning
confidence: 99%